THE EFFECT OF WORK TRAINING AND WORK DISCIPLINE ON PERFORMANCE OF PT. PLASINDO SUSTAINABLE KARAWANG - Suherman, Enjang; suroso; Purnama Sari, Dinar (International Journal Accounting Tax and Business, 2021)
Abstract PT. Plasindo Lestari Karawang, who stated that there are two training methods commonly used by companies, namely: internal training and external training. Training alone is not enough, work discipline can also be said as an effort to improve employee performance. The purpose of this study is to analyze how job training and work discipline affect employee performance. The research method used in this research is descriptive and verification method. The population in this study is the division of PGA and Project employees as many as 113 employees of the total employees of PT. Plasindo Lestari Karawang as many as 1200 employees. The determination of the sample in this study was carried out randomly from members of the population and was obtained using the Slovin formula, which is 86. The verification analysis method carried out in this study was by using Multiple Regression Model analysis (Multiple Regression). Based on the results of the descriptive analysis, it was found that job training had good criteria, work discipline had high criteria and employee performance had good criteria. Meanwhile, the results of the verification analysis show that (1) the effect of job training and work discipline has a positive and significant effect based on the t-test of 2,080 and 5,466 > t table of 1.98; (2) the effect of job training and work discipline has a positive and significant effect based on the f test count 50,039 > f table 3,10. Keywords: Job Training, Work Discipline, Employee Performance